Pengaruh metode pelelehan (thawing) terhadap mutu udang vaname (Litopenaeus vannamei) - Hafiludin Hafiludin; Fitri Hidayatun Najah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
One of the shrimp cultivated in Indonesia is the vannamei shrimp. Shrimp is a food product that is easily damaged. Therefore, good and proper handling ensures the product is of high quality and not easily damaged. The freezing process is one of the handling techniques for vannamei shrimp products. Shrimp frozen before being processed needs to be refreshed by thawing. This study aims to determine the effect of the thawing method on the quality of vannamei shrimp (Litopenaeus vannamei) physically, chemically, and biologically. The analysis used in this study included proximate, total plate count (TPC), and organoleptic analysis. The treatment of differences in the thawing method on the quality of vannamei shrimp chemically, biologically, and physically was done by soaking frozen white vannamei shrimp and draining it with running water. Analysis of the data used is the paired sample T-test (paired T-test) and the Mann-Whitney test. The results of the proximate analysis of vannamei shrimp samples with thawing rinse treatment obtained water content of 73.425% ± 0.04; ash content of 1.246% ± 0.02; fat content of 0.73% ± 0.12; and protein content of 19.515% ± 0.24. The results of the proximate analysis of vannamei shrimp samples with soaked thawing treatment obtained water content of 72.635% ± 0.43; ash content of 1.246% ± 0.05; fat content of 0.745% ± 0.12; and protein content of 19.625% ± 0.64. The results of the TPC analysis of the vannamei shrimp with rinse thawing treatment were 3.2 x 103 colonies/g, and the results of the TPC analysis of the vannamei shrimp with soaked thawing treatment were 3.0 x 103 colonies/g. The organoleptic values obtained in vannamei shrimp samples with rinse and soak thawing treatments were 8.27 and 8.03. Frozen vannamei shrimp are still fresh and safe for consumption.